2021
DOI: 10.3390/jcm10163749
|View full text |Cite
|
Sign up to set email alerts
|

Hysterolaparoscopy: A Gold Standard for Diagnosing and Treating Infertility and Benign Uterine Pathology

Abstract: Background: Combined hysteroscopy and laparoscopy is a valuable method for diagnosing and treating infertility and benign uterine pathology. Both procedures are minimally invasive, reliable, and safe, with a low complication rate. Aim: In this review, we expose the efficiency and safety of hysterolaparoscopy in the management of infertility and other benign uterine pathologies. Method: We performed a systematic literature review on several databases: PubMed®/MEDLINE, PMC, Crossref.org, and Web of Science in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 109 publications
0
15
0
Order By: Relevance
“…In our study, hysteroscopy was performed in 89% of women along with laparoscopy. The improved fertility performance and restoration by this combined hysteroscopy‐laparoscopy surgical treatment for endometriosis‐related infertility is one of the better options currently available, despite some limitations 25,26 . A previous study reported higher pregnancy rates (81.3%) and live birth rates (94.2%) after surgery and also indicated that surgical expertise and patient’s age play an important role in fertility performance rather than the endometriosis stage 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, hysteroscopy was performed in 89% of women along with laparoscopy. The improved fertility performance and restoration by this combined hysteroscopy‐laparoscopy surgical treatment for endometriosis‐related infertility is one of the better options currently available, despite some limitations 25,26 . A previous study reported higher pregnancy rates (81.3%) and live birth rates (94.2%) after surgery and also indicated that surgical expertise and patient’s age play an important role in fertility performance rather than the endometriosis stage 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The improved fertility performance and restoration by this combined hysteroscopy-laparoscopy surgical treatment for endometriosisrelated infertility is one of the better options currently available, despite some limitations. 25,26 A previous study reported higher pregnancy rates (81.3%) and live birth rates (94.2%) after surgery and also indicated that surgical expertise and patient's age play an important role in fertility performance rather than the endometriosis stage. 25 Ovarian endometriosis was found to be diagnosed preoperatively on ultrasonography in the majority of OMA cases, but other endometriotic lesions were undetected, which agreed with previous observations.…”
Section: Discussionmentioning
confidence: 99%
“…When an analysis of the overall accuracy of HSG in detecting hydrosalpinx was performed, this gave a poor result (<90%); thus, HSG may not be the best of the tools in detecting hydrosalpinx. Varlas et al 24 in their systematic review has demonstrated the importance of see-and-treat advantage of HLD in the diagnosis of hydrosalpinx.…”
Section: Discussionmentioning
confidence: 99%
“…They, however, recognised the combined procedures of laparoscopy and hysteroscopy as the gold standard for utero-tubal assessment. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Hysteroscopy is a minimally invasive endoscopic surgical procedure recognized as a "gold standard" for the evaluation of the uterine cavity, for both diagnostic and therapeutic purposes [1][2][3].…”
Section: Introductionmentioning
confidence: 99%